2023
DOI: 10.1186/s12964-022-01029-5
|View full text |Cite
|
Sign up to set email alerts
|

GRHL2-controlled gene expression networks in luminal breast cancer

Abstract: Grainyhead like 2 (GRHL2) is an essential transcription factor for development and function of epithelial tissues. It has dual roles in cancer by supporting tumor growth while suppressing epithelial to mesenchymal transitions (EMT). GRHL2 cooperates with androgen and estrogen receptors (ER) to regulate gene expression. We explore genome wide GRHL2 binding sites conserved in three ER⍺/GRHL2 positive luminal breast cancer cell lines by ChIP-Seq. Interaction with the ER⍺/FOXA1/GATA3 complex is observed, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Our results validated these findings and expanded the list of TFs that VGLL1 can potentially interact with to include TEAD2, TEAD3, RUNX2, GATA6, AP-1 and GRHL2. These TFs have been linked to the hippo pathway and epithelial tissue development, PI3K/AKT pathway activation, and the promotion of tumorigenesis ( 49 51 ). Notably, we found that VGLL1 bound mostly at intron regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results validated these findings and expanded the list of TFs that VGLL1 can potentially interact with to include TEAD2, TEAD3, RUNX2, GATA6, AP-1 and GRHL2. These TFs have been linked to the hippo pathway and epithelial tissue development, PI3K/AKT pathway activation, and the promotion of tumorigenesis ( 49 51 ). Notably, we found that VGLL1 bound mostly at intron regions.…”
Section: Discussionmentioning
confidence: 99%
“…TBP is a critical transcription factor required for promoter recognition and assembly of transcription pre-initiation complexes [ 38 ]. GRHL2 acts as an essential transcription factor for epithelial-to-mesenchymal transitions and estrogen-induced transcription in breast cancer [ 39 , 40 ]. A recent study showed that H3K27Ac-enriched genes harbor a putative GRHL transcription factor-binding site in psoriasis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors bolster epithelial attributes in both normal and neoplastic cells, chiefly by repressing the transcription of mesenchymal markers and establishing reciprocal inhibitory loops with EMT-TFs [66][67][68][69]. In addition to their regulatory roles, several MET-TFs, including CDH1, ZO-1, and those encoding claudin-4 and claudin-5 (CLDN4 and CLDN5), directly stimulate the transcription of genes that codify proteins essential for epithelial lineage specification [70,71]. These orchestrated molecular events underscore the complexity of cellular transitions during EMT and MET, highlighting the necessity for a nuanced understanding of these processes in both health and disease.…”
Section: Emt/met-inducing Transcription Factorsmentioning
confidence: 99%